An Analysis of Politeness Strategies in Movie: Flipped - Diva Aathifah Najla Fadhillah; Puspita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is identifying the types and the factors of using Politenes Strategies in the movie entitled Flipped. The analysis method that used in this study is qualititive method. There are four types of politeness strategies found in this study, including Bald-On (33,3%), Positive Politeness (26,66%), Negative Politeness (20%), Off-Record (20%). And on the other hand, there are three factors found in this study, namely Power (20%), Social Distance (46,67%) and Rank of Imposition. (33,33)%